تأثير تدریبات كروس فيت فی القدره‌ الهوائیه‌ واللاهوائیه‌ وبعض المتغیرات البدنیه‌ لدی الشباب بكرة اليد البحث مستل من رسالة الماجستير - غفوری, ریباز بایز توفیق; فرنسی, هه‌وار بطرس (Sulaimani Journal for Humanities, 2023)
Introduction and Research Problem: Crossfit Training Is One of The Exercises That Has Recently Entered the Field of Sports Training and Has Spread Widely. Crossfit Is Actually the Name of a Sports Company Founded by Greg Glassman And Lauren Jenai in 2000. (Swedish) Weight-Lifting Exercises and Gymnastics. Crossfit Training Is One of The Most Prominent Exercises That Increase Muscle Endurance, Which Is A Circular Group of Exercises That Train the Basic Muscles in The Body. Abdominal Exercises, Running, Pull-Up Exercises, Weight-Lifting Training, Aerobics Training, Gymnastics, Kettle Bell Exercises, Battle Rope Exercises, And Plyosoft Box Exercises, And These Exercises Are Practiced by Repetition Without Stopping or Passive Rest, Throughout the Specified Training Unit. Aerobic and Anaerobic Capacity and Some Physical Variables Among Young Handball Players. It Included The Research Problem, Which Lies In The Fact That The Exercises Used To Develop Physical Fitness Depend Greatly On The Amount Of Individual Performance For The Exercises Given To Him Without Paying Attention To The Element Of Competition, Which Is A Major Element In Crossfit) Exercises, Which Provides An Important Incentive For Continuity In Performance And Thus Work To Develop The Level Of Physical Fitness And Physiological For Young People In Sports Clubs, As A Basis For The Training Process. As For The Areas Of Research, The Human Field Included A Sample Of The Youth Of The Koya Sports Club In Handball, And The Researcher Used The Experimental Approach In The Manner Of The Two Equal Groups (Control And Experimental), As The Number Of Members Of The Research Sample Was (14) Players, As The Sample Was Divided Into Two Groups, And The Researcher Took Into Account The Homogeneity And Equivalence Of The Sample Research In The Variables Under Study, And After Conducting The Pre-Tests, The Exercises Were Applied To The Research Sample Using Crossfit Exercises, And The Exercises Lasted For The Two Groups (12) Weeks, At An Average Of Three Training Units Per Week, And The Time Of The Training Unit Was (54.5-105) Minutes, And After The Completion Of The Exercises For The Two Groups, Post-Tests Were Performed, And Statistical Data Were Processed Using The Spss System. By Discussing The Results Presented, The Researcher Reached Several Conclusions, The Most Important Of Which Are: - The Effectiveness Of The Training Curriculum According To Crossfit Training In Developing All Physical And Physiological Indicators (Aerobic Capacity And Anaerobic Capacity). - The Members Of The Experimental Group That Were Trained According To Crossfit Exercises Were Superior To The Members Of The Control Group That Were Trained According To The Training Method Used In The Tests Of The Strength Characteristic Of Speed For The Arms, The Strength Characteristic Of Speed For The Legs, The Explosive Force Of The Lower Extremities, The Speed Of The Motor Response, The Aerobic Capacity And The Anaerobic Capacity.